2020
DOI: 10.26434/chemrxiv.13353473.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary Metabolites from Caulerpa Cylindracea (Sonder) Could Be Alternative Natural Antiviral Compounds for COVID-19: A Further in Silico Proof

Abstract: <p>SARS-CoV-2 has been exhibiting extremely spreading property all around the world since its existence from Wuhan-China in December-2019. Although it has caused a death toll of over than 1.3 M people, no validated vaccine has been proposed yet. On the other hand, very dense studies on the vaccine development have been carrying out in some countries such as the US, Germany, UK, China and Russia. Due to side effects of current antiviral agents used in the therapy of COVID-19, there is a great need for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Also, according to their molecular dynamics results, caulerpin makes intermolecular H-bonds with S289 (VI) and S342/R288 (V) ( Vitale et al, 2018 ). Furthermore, antiviral activity of caulerpin against SARS-CoV-2 was tested using in-silico tools ( Abdelrheem et al, 2020 ; Ahmed et al, 2020 ; Çavaş et al, 2020 ; El-Mageed et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, according to their molecular dynamics results, caulerpin makes intermolecular H-bonds with S289 (VI) and S342/R288 (V) ( Vitale et al, 2018 ). Furthermore, antiviral activity of caulerpin against SARS-CoV-2 was tested using in-silico tools ( Abdelrheem et al, 2020 ; Ahmed et al, 2020 ; Çavaş et al, 2020 ; El-Mageed et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[7]; inhibition of monoamine oxidase-B [8], antituberculosis activity [9]; and antinociception [10] activities. Furthermore, it was stated by in silico studies that it has antiviral activity against bovine viral diarrhea virus, herpes simplex virus, chikungunya virus, and SARS-CoV-2 [11][12][13][14][15][16][17]. It was reported that caulerpin has a hepatocellular carcinoma peroxisome proliferator activating receptor alpha and peroxisome proliferator activating receptor gamma activity in vivo and in vitro [18].…”
Section: Introductionmentioning
confidence: 99%